Sintered foil for anode material of aluminum electrolytic capacitor and preparation method of sintered foil

By coating high-melting oxide or ceramic particles with anti-blocking slurry in the blank area of ​​the aluminum foil, the adhesion between the aluminum foil layers is blocked, and the adhesion problem of sintered foil is solved, and the product quality and electrochemical performance of the capacitor are improved.

CN119153236AInactive Publication Date: 2024-12-17SHEN ZHEN SHI JIN FU KANG DIAN ZI YOU XIAN GONG SI
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411310938.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the sintering process of aluminum electrolytic capacitors, atomic diffusion caused by high temperatures between the base aluminum foils lead to adhesion, resulting in the problem of edge tearing and foil breaking when the rolled foil is separated, and the prior art is complex and leads to energy waste.

Method used

Leave blank areas on the left and right sides of the base aluminum foil without coating aluminum powder slurry, while coating anti-blocking slurry containing oxide particles or ceramic particles higher than the aluminum melting point in the blank areas for drying, sintering and melting The treatment is made to form an anti-adhesive layer, blocking the diffusion of aluminum atoms.

Benefits of technology

It effectively reduces the tearing and foil breaking during coil separation, improves the yield of sintered foil, enhances the mechanical strength of the edges of the aluminum foil, ensures the uniformity and density of the alumina film, and extends the service life of the capacitor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153236A_ABST
    Figure CN119153236A_ABST
Patent Text Reader

Abstract

According to the preparation method for the positive electrode material of the aluminum electrolytic capacitor, the base material aluminum foil is not fully coated with the aluminum powder slurry, but blank areas are reserved on the left side and the right side, the blank areas are coated with a layer of anti-sticking slurry containing oxide particles or ceramic particles with the melting point higher than that of aluminum, and the melting point of the particles is higher than that of the aluminum; diffusion among aluminum atoms can be effectively blocked, an anti-sticking layer is formed, and adhesion between adjacent aluminum foil layers is prevented; due to the use of the anti-sticking slurry, the adhesive force between the aluminum foil layers is reduced, so that the occurrence of tearing and wrinkling in the processes of coil dividing, sintering, formation and subsequent treatment is reduced, the reliability of the aluminum electrolytic capacitor is improved, and the service life of the aluminum electrolytic capacitor is prolonged; according to the anti-adhesion sintered foil manufactured through the method, the width of the blank area is preferably 5-20 mm, and the design guarantees the sufficient anti-adhesion effect and does not affect the effective use area of the aluminum foil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sintered foils, in particular to a sintered foil for positive electrode materials of aluminum electrolytic capacitors and a preparation method thereof. Background Art

[0002] As a basic device of electronic components, aluminum electrolytic capacitors are widely used in electronic circuit fields such as industrial frequency conversion and power supply. Among them, the positive electrode foil is the key material of aluminum electrolytic capacitors, which is directly related to the various parameters and service life of the capacitor. The production process of positive electrode foil is mainly divided into two types: corrosion process and sintering process. The sintering process refers to coating aluminum powder slurry on both surfaces of the base aluminum foil, rolling it into a foil roll after drying, and then sintering the whole roll at high temperature, and finally undergoing chemical treatment to obtain the positive electrode foil for aluminum electrolytic capacitors.

[0003] During the sintering process, the base aluminum foil coated with aluminum powder slurry is usually dried and rolled into a coiled foil for sintering under certain temperature conditions. However, due to the atomic diffusion of the aluminum powder on the base aluminum foil under high temperature conditions during the sintering process, the base aluminum foils of adjacent layers in the coiled foil are adhered, resulting in the phenomenon of edge tearing or even foil breaking during the coiling process of the sintered foil, which seriously affects the quality and yield of the product.

[0004] The inventors have observed on the basis of a large number of experiments that the adhesion phenomenon of the sintered foil after sintering is mainly concentrated on the two side edges of the rolled foil, which leads to the tearing and breaking of the foil when the foil is rolled. In the prior art, there is a method to solve the adhesion problem by adding a layer of alloy foil with a melting point higher than that of aluminum in the interlayer when the foil is rolled. However, this method not only has complex equipment, but also leads to an increase in the volume of each rolled foil, resulting in a waste of energy during high-temperature sintering. Therefore, the inventors propose a sintered foil for positive electrode material of aluminum electrolytic capacitors and a preparation method thereof to solve the above-mentioned problem. Summary of the invention

[0005] In view of the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a sintered foil for positive electrode materials of aluminum electrolytic capacitors, which is used to solve the problem of adhesion between adjacent layers of aluminum foil in the rolled foil in the prior art, resulting in edge tearing and foil breakage of the sintered foil during the rolling process. At the same time, the present invention will also provide a sintered foil for positive electrode materials of aluminum electrolytic capacitors prepared by the preparation method.

[0006] To achieve the above purposes and other related purposes,

[0007] The first aspect of the present invention provides a method for preparing a sintered foil for positive electrode materials of aluminum electrolytic capacitors, comprising the following steps: S1, preparing aluminum powder slurry, coating the aluminum powder slurry on the front and back sides of a substrate aluminum foil, and leaving blank areas on the left and right sides of the substrate aluminum foil without coating the aluminum powder slurry; S2, preparing an anti-sticking slurry, the anti-sticking slurry comprising oxide particles or ceramic particles above the melting point of aluminum, a solvent, a binder and an auxiliary agent; S3, coating the anti-sticking slurry in the blank area, and the coating thickness of the anti-sticking slurry is less than or equal to the coating thickness of the aluminum powder slurry; S4, drying the aluminum foil coated with the aluminum powder slurry and the anti-sticking slurry; S5, rolling the dried aluminum foil into a coiled foil, and sintering the coiled foil under high temperature conditions; S6, performing a chemical treatment on the sintered coiled foil and cleaning and drying it to obtain a sintered foil for positive electrode materials of aluminum electrolytic capacitors.

[0008] In one embodiment of the present invention, the anti-sticking slurry includes 50-60 wt % of oxide particles or ceramic particles, 30-40 wt % of solvent, 5-15 wt % of binder, and 1-5 wt % of auxiliary agent.

[0009] In one embodiment of the present invention, the oxide particles are one or more of aluminum oxide, zirconium oxide, magnesium oxide, and titanium oxide; and the ceramic particles are one or more of silicon dioxide, silicon nitride, silicon carbide, titanium carbide, and boron carbide.

[0010] In one embodiment of the present invention, the solvent is selected from one or more of terpineol, tributyl citrate and phthalate; the binder is selected from one or more of ethyl cellulose, polyacrylate and polyethylene resin; the auxiliary agent includes a dispersant, a leveling agent, a defoaming agent, a stabilizer, a coupling agent and a pH regulator.

[0011] In one embodiment of the present invention, the dispersant is one or more of sodium phosphate, sodium silicate, sodium carbonate, sodium metasilicate, sodium citrate, sodium humate, sodium polyacrylate or polyacrylamide; the leveling agent is one or more of polyacrylates, polyurethanes, siloxanes or acrylate copolymers; the defoamer is one or more of silicones, phosphates, polyethers, phosphates or amides; the stabilizer is one or more of carboxymethyl cellulose, ethyl cellulose, polypropylene carbonate or dimethyl adipate; the coupling agent is one of silane coupling agent, titanate coupling agent, aluminate coupling agent, phosphate coupling agent or zirconate coupling agent; the pH adjuster is one or more of diammonium phosphate, phosphoric acid, oxalic acid and acetic acid.

[0012] In one embodiment of the present invention, the width of the blank area is 1-50 mm, preferably 5-20 mm.

[0013] In one embodiment of the present invention, the chemical formation treatment includes low-pressure chemical formation, medium-pressure chemical formation and high-pressure chemical formation; in the low-pressure chemical formation, the sintered coil foil is immersed in an aqueous solution containing 1.2-1.8 mol / L phosphoric acid, 0.5-1 mol / L ammonium adipate, and 0.1-0.3 mol / L boric acid, and a voltage of 100-200 V is passed through the chemical formation solution to control the current density to 1-5 A / dm 2 , control the forming temperature to 50℃-70℃, and the forming time to 0.5-1h; medium pressure forming, immerse the coiled foil after low pressure forming in an aqueous solution containing 1-2mol / L sulfuric acid, 0.6-1.2mol / L sebacic acid, and 0.1-0.5mol / L citric acid, pass a voltage of 200-400V in the forming solution, and control the current density to 3-6A / dm 2 , control the forming temperature to 60-80℃, the forming time to 0.5-1h; high pressure forming, immerse the coiled foil after medium pressure forming in an aqueous solution containing 1-2mol / L sulfuric acid, 0.5-1.5mol / L citric acid, and 0.3-0.8mol / L boric acid, pass a voltage of 400-600V in the forming solution, and control the current density to 5-10A / dm 2 , control the formation temperature to 70-90℃, and the formation time to 1-2h.

[0014] In one embodiment of the present invention, the sintering process is carried out under nitrogen or inert atmosphere, and the pressure is controlled to be 0.1-1 atmospheres; during sintering, the temperature in the sintering furnace is first raised to 300-400°C, and the time is controlled to be 1-2 hours, and then the temperature is gradually raised to 500-600°C, and the sintering time is controlled to be 9-11 hours; after sintering, the cooling rate is controlled to not exceed 10°C / min until the temperature drops below 200°C, and then the sintered coil foil is taken out and cooled to room temperature.

[0015] In one embodiment of the present invention, the temperature of the drying treatment in S4 is 80-120° C., the drying time is 15-45 min, and the protective atmosphere is nitrogen or an inert gas.

[0016] A second aspect of the present invention provides a sintered foil for positive electrode material of aluminum electrolytic capacitors, wherein the sintered foil is prepared by the preparation method according to any one of claims 1 to 9.

[0017] As described above, the sintered foil for positive electrode material of aluminum electrolytic capacitor and the preparation method thereof of the present invention have the following beneficial effects: when the aluminum foil of the base material is coated with aluminum powder slurry, the present invention does not fully coat it, but leaves blank areas on the left and right sides, and coats the blank areas of the aluminum foil with anti-sticking slurry containing high melting point oxide particles or ceramic particles. The anti-sticking slurry can remain solid during high-temperature sintering and effectively block the diffusion of aluminum atoms, thereby preventing adhesion between aluminum foil layers, thereby effectively reducing tearing and foil breaking during winding, and significantly improving the yield rate of the sintered foil; the anti-sticking slurry not only prevents adhesion, but also enhances the mechanical strength of the edge of the aluminum foil to a certain extent, reducing The tearing and wrinkling caused by external force during winding and use are prevented; the width of the blank area is designed to be 1-50mm, preferably 5-20mm, which ensures sufficient anti-sticking effect without affecting the effective use area of ​​the aluminum foil; a uniform and dense aluminum oxide film is gradually formed through three stages of low-pressure formation, medium-pressure formation and high-pressure formation, which ensures the uniformity and density of the film, improves the electrochemical properties of the capacitor, reduces leakage current, and extends the service life of the capacitor; the formulations of the formation liquid and the process parameters of the different stages are reasonably designed, which can effectively control the formation process of the aluminum oxide film and ensure that the film has good dielectric properties and mechanical strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Shown is a schematic diagram of a method for preparing a sintered foil for positive electrode material of an aluminum electrolytic capacitor provided by the present invention. DETAILED DESCRIPTION

[0019] The following is a description of the implementation of the present invention by means of specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.

[0020] The present invention provides a method for preparing a sintered foil for positive electrode materials of aluminum electrolytic capacitors, comprising the following steps: S1, preparing aluminum powder slurry, coating the aluminum powder slurry on both sides of a substrate aluminum foil, and leaving blank areas on the left and right sides of the substrate aluminum foil without coating the aluminum powder slurry; S2, preparing an anti-sticking slurry, wherein the anti-sticking slurry comprises oxide particles or ceramic particles having a melting point higher than that of aluminum, a solvent, a binder and an auxiliary agent; S3, coating the anti-sticking slurry in the blank area, wherein the coating thickness of the anti-sticking slurry is less than or equal to the coating thickness of the aluminum powder slurry; S4, drying the aluminum foil coated with the aluminum powder slurry and the anti-sticking slurry; S5, rolling the dried aluminum foil into a coiled foil, and sintering the coiled foil under high temperature conditions; S6, performing a chemical treatment on the sintered coiled foil and washing and drying it to obtain a sintered foil for positive electrode materials of aluminum electrolytic capacitors.

[0021] Aluminum powder slurry is coated on both sides of the base aluminum foil to increase the specific surface area of ​​the aluminum foil and improve its electrochemical activity. The aluminum powder slurry will form a porous structure in the subsequent sintering process, which is conducive to the penetration of electrolyte and the storage of charge. The anti-sticking slurry contains oxide particles or ceramic particles above the melting point of aluminum. The melting point of these particles is higher than that of aluminum, which can effectively block the diffusion between aluminum atoms and form an anti-sticking layer to prevent the adhesion between adjacent aluminum foil layers. The coated aluminum foil needs to be dried to remove the solvent in the slurry. The drying process is carried out under a protective atmosphere to avoid oxidation. The sintering process is carried out under high temperature conditions so that the aluminum powder particles in the aluminum powder slurry are combined with each other to form a stable porous structure. At the same time, the oxide particles or ceramic particles in the anti-sticking slurry will form an anti-sticking layer in the blank area of ​​the aluminum foil to prevent the aluminum foil from sticking during sintering. The sintered aluminum foil is subjected to a chemical treatment to form a uniform aluminum oxide film on the surface of the aluminum foil through electrolysis, further improving the electrochemical properties of the aluminum foil.

[0022] By coating the blank area of ​​the aluminum foil with an anti-sticking slurry containing oxide particles or ceramic particles with a temperature higher than the melting point of aluminum, an effective anti-sticking layer is formed, which prevents the adjacent aluminum foil layers from sticking together during the sintering process and improves the product's qualified rate. The use of the anti-sticking slurry reduces the adhesion between the aluminum foil layers, thereby reducing the occurrence of tearing and wrinkling during the winding, sintering, formation and subsequent processing, and improving the reliability and service life of the aluminum electrolytic capacitor.

[0023] The anti-sticking slurry includes 50-60wt% of oxide particles or ceramic particles, 30-40wt% of solvent, 5-15wt% of binder, and 1-5wt% of auxiliary agent. Oxide particles or ceramic particles are the main components of the anti-sticking slurry. These high-melting point particles remain solid during the sintering process. They provide a physical barrier at high temperatures, block the diffusion path of aluminum atoms, and effectively prevent adhesion between aluminum foil layers. The solvent is used to adjust the viscosity and fluidity of the anti-sticking slurry so that it is easy to coat on the designated area of ​​the aluminum foil. The binder ensures good adhesion between the oxide or ceramic particles and the aluminum foil substrate; the auxiliary agent is used to improve the processing performance of the slurry, such as preventing particle aggregation and improving the uniformity and stability of the coating.

[0024] The oxide particles are one or more of aluminum oxide, zirconium oxide, magnesium oxide, and titanium oxide; the ceramic particles are one or more of silicon dioxide, silicon nitride, silicon carbide, titanium carbide, and boron carbide.

[0025] Oxide particles and ceramic particles are dispersed on the surface of the aluminum foil in a certain proportion to prevent adhesion between aluminum foil layers. The melting point of these oxide particles or ceramic particles is usually much higher than the melting point of aluminum (660°C), so they can remain stable during the sintering process.

[0026] The solvent is selected from one or more of terpineol, tributyl citrate and phthalate; the binder is selected from one or more of ethyl cellulose, polyacrylate and polyethylene resin; the auxiliary agent includes a dispersant, a leveling agent, a defoamer, a stabilizer, a coupling agent and a pH regulator.

[0027] The solvent is selected from one or more of terpineol, tributyl citrate and phthalate, which play a key role in the electronic paste. They provide polar groups and ensure that the solid powder or particles can be evenly dispersed therein; the binder helps the oxide particles and ceramic particles to combine with the substrate aluminum foil during the sintering process, and increases the adhesion and mechanical strength of the anti-sticking layer; the auxiliary agent is used to improve the processing properties of the anti-sticking slurry, such as preventing particle aggregation and improving the uniformity and stability of the coating.

[0028] The dispersant is one or more of sodium phosphate, sodium silicate, sodium carbonate, sodium metasilicate, sodium citrate, sodium humate, sodium polyacrylate or polyacrylamide; the leveling agent is one or more of polyacrylate, polyurethane, siloxane or acrylate copolymer; the defoamer is one or more of silicone, phosphate, polyether, phosphate or amide; the stabilizer is one or more of carboxymethyl cellulose, ethyl cellulose, polypropylene carbonate or dimethyl adipate; the coupling agent is one of silane coupling agent, titanate coupling agent, aluminate coupling agent, phosphate coupling agent or zirconate coupling agent; the pH adjuster is one or more of diammonium phosphate, phosphoric acid, oxalic acid and acetic acid.

[0029] Dispersants help prevent particle aggregation and improve the uniformity of the slurry; leveling agents are used to improve the surface quality after coating and reduce unevenness and holes; defoaming agents are used to reduce bubbles in the slurry and improve coating quality; stabilizers are used to maintain the stability of the slurry and prevent separation and precipitation; coupling agents are used to improve the adhesion between oxide or ceramic particles and the aluminum foil substrate; among the auxiliary agents, dispersants, leveling agents, defoamers, stabilizers, and coupling agents are alkaline, so acidic pH adjusters are used to adjust the pH value of the slurry to control the pH value of the slurry and improve the coating effect.

[0030] The width of the blank area is 1-50 mm, preferably 5-20 mm. The width of the blank area is designed to be 1-50 mm, preferably 5-20 mm. This design not only ensures sufficient anti-sticking effect, but also does not affect the effective use area of ​​the aluminum foil; the anti-sticking layer formed by the anti-sticking slurry not only prevents adhesion, but also enhances the strength of the edge of the aluminum foil, reduces the tearing and wrinkling caused by external forces during winding and use, and improves the yield and quality of the product.

[0031] The chemical formation treatment includes low-pressure chemical formation, medium-pressure chemical formation and high-pressure chemical formation. In the low-pressure chemical formation, the sintered coil foil is immersed in an aqueous solution containing 1.2-1.8 mol / L phosphoric acid, 0.5-1 mol / L ammonium adipate and 0.1-0.3 mol / L boric acid, and a voltage of 100-200 V is passed through the chemical formation solution to control the current density to 1-5 A / dm 2 , control the forming temperature to 50℃-70℃, and the forming time to 0.5-1h; medium pressure forming, immerse the coiled foil after low pressure forming in an aqueous solution containing 1-2mol / L sulfuric acid, 0.6-1.2mol / L sebacic acid, and 0.1-0.5mol / L citric acid, pass a voltage of 200-400V in the forming solution, and control the current density to 3-6A / dm 2 , control the forming temperature to 60-80℃, the forming time to 0.5-1h; high pressure forming, immerse the coiled foil after medium pressure forming in an aqueous solution containing 1-2mol / L sulfuric acid, 0.5-1.5mol / L citric acid, and 0.3-0.8mol / L boric acid, pass a voltage of 400-600V in the forming solution, and control the current density to 5-10A / dm 2 , control the formation temperature to 70-90℃, and the formation time to 1-2h.

[0032] Phosphoric acid's main role in the chemical process is to promote the formation of aluminum oxide film. The presence of phosphoric acid can also help control the thickness and uniformity of the oxide layer. Ammonium adipate acts as a buffer in the chemical solution, adjusting the pH value of the chemical solution to keep it within an appropriate range and helping to improve the density of the film. Boric acid can inhibit local overheating and prevent uneven formation of the oxide layer. Sulfuric acid can accelerate the oxidation reaction on the surface of the aluminum foil to form a thicker and denser oxide layer. Sebacic acid can improve the uniformity of the oxide layer and reduce defects. Citric acid acts as a chelating agent in the chemical solution, which can form a stable complex with metal ions, thereby reducing the precipitation of metal ions in the chemical solution, helping to maintain the stability of the chemical solution, and helping to improve the quality of the oxide layer.

[0033] The purpose of low-pressure formation is to initially form an aluminum oxide film, laying the foundation for subsequent formation; in medium-pressure formation, a higher current density and temperature are used to promote the growth of the oxide film, further thicken the aluminum oxide film, and improve its structure to make it more compact; the purpose of high-pressure formation is to eventually form a uniform aluminum oxide film with good electrochemical properties to ensure the long-term stability and reliability of the capacitor. The aluminum oxide film is gradually formed through three stages of low-pressure formation, medium-pressure formation and high-pressure formation, ensuring the uniformity and compactness of the film and improving the electrochemical performance of the capacitor; the formulation of the formation liquid and the process parameters at different stages are reasonably designed, which can effectively control the formation process of the aluminum oxide film and ensure that the film has good dielectric properties and mechanical strength; through multiple formation treatments, the reliability of aluminum electrolytic capacitors can be significantly improved, leakage current can be reduced, and the service life of capacitors can be extended; step-by-step formation treatment helps to improve the withstand voltage and capacitance value of aluminum electrolytic capacitors, thereby improving the overall performance of capacitors.

[0034] The sintering process is carried out under nitrogen or inert atmosphere, and the pressure is controlled to be 0.1-1 atmospheres. During sintering, the temperature in the sintering furnace is first raised to 300-400°C, and the time is controlled to be 1-2 hours, and then the temperature is gradually raised to 500-600°C, and the sintering time is controlled to be 9-11 hours. After sintering, the cooling rate is controlled to be no more than 10°C / min until the temperature drops below 200°C, and then the sintered coil foil is taken out and cooled to room temperature.

[0035] The sintering process is carried out under nitrogen or inert atmosphere (such as argon). This atmosphere control is to prevent the aluminum foil from oxidizing at high temperatures and maintain the purity of the material and the expected electrochemical properties. It is maintained for 1-2 hours. The purpose of this stage is to gradually adapt the aluminum foil to the high temperature environment, while allowing the organic components such as binders and solvents to begin to decompose and volatilize. The sintering time is controlled to be 9-11 hours. Long-term sintering treatment helps to fully combine the aluminum powder particles, form a stable porous structure, and improve the electrochemical properties of the material. After sintering, the cooling rate is controlled to not exceed 10℃ / min until the temperature drops below 200℃. Slow cooling helps to reduce the stress inside the material and avoid the risk of cracks or deformation that may be caused by rapid cooling.

[0036] The drying temperature in S4 is 80-120°C, the drying time is 15-45 minutes, and the protective atmosphere is nitrogen or inert gas. The drying temperature is controlled within the range of 80-120°C. This temperature range can ensure the effective evaporation of the solvent while avoiding excessive temperature causing thermal damage to the material or premature curing of the binder; by controlling the drying temperature and time, the coated slurry can be uniformly cured to form a stable coating, thereby improving the consistency and reliability of the final product.

[0037] The present invention also includes a sintered foil for positive electrode material of aluminum electrolytic capacitors prepared according to the above preparation method. The sintered foil prepared by the preparation method has high specific capacitance, good mechanical properties and excellent electrochemical stability. Anti-sticking slurry is coated on the blank area of ​​the aluminum foil to form an effective anti-sticking layer, which prevents adhesion between adjacent aluminum foil layers and reduces the risk of tearing and wrinkling.

[0038] Embodiment 1

[0039] The aluminum powder slurry is coated on both sides of the substrate aluminum foil, and a blank area of ​​5 mm is left on the left and right sides of the substrate aluminum foil, and the anti-sticking slurry is coated in the blank area, and the coating thickness of the anti-sticking slurry is less than or equal to the coating thickness of the aluminum powder slurry. The aluminum foil coated with the aluminum powder slurry and the anti-sticking slurry is dried, and the dried aluminum foil is rolled into a foil roll, and the foil roll is sintered under high temperature conditions; the sintered foil roll is chemically treated and cleaned and dried to obtain a sintered foil for the positive electrode material of an aluminum electrolytic capacitor.

[0040] The anti-sticking slurry comprises 50wt% of aluminum oxide, 40wt% of terpineol, 10wt% of ethyl cellulose, and 3wt% of an auxiliary agent;

[0041] The drying temperature is 100°C, the drying time is 30 minutes, the protective atmosphere is nitrogen, and the pressure is controlled at 0.1-1 atmospheres during the sintering process. During sintering, the temperature in the sintering furnace is first raised to 300-400°C for 1 hour, and then gradually raised to 500-600°C, and the sintering time is controlled to 10 hours; after sintering, the cooling rate is controlled not to exceed 10°C / min until the temperature drops below 200°C, and then the sintered coil foil is taken out and cooled to room temperature.

[0042] The chemical treatment includes low-pressure chemical treatment, medium-pressure chemical treatment and high-pressure chemical treatment. In low-pressure chemical treatment, the sintered coil foil is immersed in an aqueous solution containing 1.5 mol / L phosphoric acid, 0.8 mol / L ammonium adipate and 0.2 mol / L boric acid, and a voltage of 150 V is passed through the chemical solution to control the current density to 3 A / dm 2 , control the forming temperature to 50℃-70℃, and the forming time to 0.5h; medium pressure forming, immerse the coiled foil after low pressure forming in an aqueous solution containing 1.5mol / L sulfuric acid, 1mol / L sebacic acid, and 0.3mol / L citric acid, pass a voltage of 300V in the forming solution, and control the current density to 5A / dm 2 , control the forming temperature to 60-80℃, the forming time to 0.5h; high pressure forming, immerse the coiled foil after medium pressure forming in an aqueous solution containing 1.5mol / L sulfuric acid, 1mol / L citric acid, and 0.5mol / L boric acid, pass a voltage of 600V in the forming solution, and control the current density to 8A / dm2 , control the formation temperature to 80℃ and the formation time to 1.5h.

[0043] In this embodiment, the rolled foil can be easily unrolled after sintering, no adhesion occurs between adjacent layers of aluminum foil, and no edge wrinkles, tears or broken foil occurs after the rolled foil is unrolled.

[0044] Embodiment 2

[0045] The difference from Example 1 is that 50 wt % of alumina contained in the anti-sticking slurry in Example 1 is replaced by 50 wt % of silica.

[0046] In this embodiment, the sintered rolled foil can be easily unrolled, and there is no adhesion between adjacent layers of aluminum foil. There is no edge tearing or foil breakage after rolling, which indicates that oxide particles or ceramic particles above the melting point of aluminum can effectively form an anti-sticking layer, which can effectively reduce the adhesion between the edge aluminum foil layers.

[0047] Embodiment 3

[0048] The difference from Example 1 is that the 50 wt % of alumina contained in the anti-sticking slurry in Example 1 is replaced by 60 wt % of silicon dioxide, and the 40 wt % of terpineol is replaced by 30 wt % of terpineol.

[0049] In this embodiment, the sintered rolled foil can be easily unrolled, and there is no adhesion between adjacent layers of aluminum foil. There is no edge tearing or foil breakage after rolling, indicating that 50-60wt% of oxide particles or ceramic particles and 30-40wt% of solvent can meet the anti-sticking requirements between aluminum foils.

[0050] Embodiment 4

[0051] Different from the first embodiment, a blank area of ​​1 mm is left on the left and right sides of the substrate aluminum foil, and an anti-sticking slurry is coated.

[0052] In this embodiment, the rolled foil can be easily unrolled after sintering, and there is no adhesion between adjacent layers of aluminum foil. However, slight wrinkles will appear on the edges after unrolling, indicating that the 1 mm area is not the best choice.

[0053] Embodiment 5

[0054] Different from the first embodiment, a blank area of ​​20 mm is left on the left and right sides of the aluminum foil substrate, and an anti-sticking slurry is coated.

[0055] In this embodiment, the sintered rolled foil can be easily unrolled, no adhesion occurs between adjacent layers of aluminum foil, and no edge wrinkles, tears or broken foil occurs after rolling, indicating that the blank distance has an obvious anti-adhesion effect.

[0056] Embodiment 6

[0057] Different from the first embodiment, a blank area of ​​50 mm is left on the left and right sides of the aluminum foil of the substrate, and an anti-sticking slurry is coated.

[0058] In this embodiment, the rolled foil can be easily unrolled after sintering, and there is no adhesion between adjacent layers of aluminum foil. There is no edge wrinkling, tearing or broken foil after rolling. However, compared with Embodiment 1 and Embodiment 4, the distance of the blank area is too large, which affects the effective use area of ​​the aluminum foil.

[0059] In summary, the present invention does not fully coat the aluminum foil substrate with aluminum powder slurry, but leaves blank areas on the left and right sides, and coats the blank areas of the aluminum foil with an anti-sticking slurry containing high-melting-point oxide particles or ceramic particles. The anti-sticking slurry can remain solid during high-temperature sintering and effectively block the diffusion of aluminum atoms, thereby preventing adhesion between aluminum foil layers, thereby effectively reducing tearing and foil breakage during winding, and significantly improving the yield rate of sintered foil; the anti-sticking slurry not only prevents adhesion, but also enhances the mechanical strength of the edge of the aluminum foil to a certain extent, reducing tearing caused by external forces during winding and use. and wrinkle phenomenon; the width of the blank area is designed to be 1-50mm, preferably 5-20mm, this design ensures sufficient anti-sticking effect without affecting the effective use area of ​​the aluminum foil; a uniform and dense aluminum oxide film is gradually formed through three stages of low-pressure formation, medium-pressure formation and high-pressure formation, which ensures the uniformity and density of the film, improves the electrochemical properties of the capacitor, reduces leakage current, and extends the service life of the capacitor; the formulation of the formation solution and the process parameters of different stages are reasonably designed, which can effectively control the formation process of the aluminum oxide film and ensure that the film has good dielectric properties and mechanical strength.

[0060] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. All equivalent modifications or changes made by those skilled in the art without departing from the spirit and technical ideas disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing a sintered foil for positive electrode material of an aluminum electrolytic capacitor, characterized in that: The following steps are involved: S1, preparing aluminum powder slurry, coating the aluminum powder slurry on the front and back sides of the substrate aluminum foil, and leaving blank areas on the left and right sides of the substrate aluminum foil without coating the aluminum powder slurry; S2, preparing an anti-sticking slurry, wherein the anti-sticking slurry comprises oxide particles or ceramic particles having a melting point higher than that of aluminum, a solvent, a binder and an auxiliary agent; S3, coating the anti-sticking slurry in the blank area, and the coating thickness of the anti-sticking slurry is less than or equal to the coating thickness of the aluminum powder slurry; S4, drying the aluminum foil coated with the aluminum powder slurry and the anti-sticking slurry; S5, rolling the dried aluminum foil into a foil roll, and sintering the foil roll under high temperature conditions; S6, after the sintered coil foil is subjected to chemical treatment and then cleaned and dried, a sintered foil for positive electrode material of aluminum electrolytic capacitor is obtained.

2. The method for preparing a sintered foil for positive electrode material of an aluminum electrolytic capacitor according to claim 1, characterized in that: The anti-sticking slurry comprises 50-60 wt % of oxide particles or ceramic particles, 30-40 wt % of solvent, 5-15 wt % of binder, and 1-5 wt % of auxiliary agent.

3. The method for preparing a sintered foil for positive electrode material of an aluminum electrolytic capacitor according to claim 1, characterized in that: The oxide particles are one or more of aluminum oxide, zirconium oxide, magnesium oxide, and titanium oxide; the ceramic particles are one or more of silicon dioxide, silicon nitride, silicon carbide, titanium carbide, and boron carbide.

4. The method for preparing a sintered foil for positive electrode material of an aluminum electrolytic capacitor according to claim 2, characterized in that: The solvent is selected from one or more of terpineol, tributyl citrate and phthalate; The binder is selected from one or more of ethyl cellulose, polyacrylate and polyethylene resin; The auxiliary agents include dispersants, leveling agents, defoamers, stabilizers, coupling agents and pH regulators.

5. The method for preparing a sintered foil for positive electrode material of an aluminum electrolytic capacitor according to claim 4, characterized in that: The dispersant is one or more of sodium phosphate, sodium silicate, sodium carbonate, sodium metasilicate, sodium citrate, sodium humate, sodium polyacrylate or polyacrylamide; The leveling agent is one or more of polyacrylates, polyurethanes, siloxanes or acrylate copolymers; The defoamer is one or more of silicone, phosphate, polyether, phosphate or amide; The stabilizer is one or more of carboxymethyl cellulose, ethyl cellulose, polypropylene carbonate or dimethyl adipate; The coupling agent is one of a silane coupling agent, a titanate coupling agent, an aluminate coupling agent, a phosphate coupling agent or a zirconate coupling agent; The pH adjuster is one or more of diammonium phosphate, phosphoric acid, oxalic acid, and acetic acid.

6. The method for preparing a sintered foil for positive electrode material of an aluminum electrolytic capacitor according to claim 1, characterized in that: The width of the blank area is 1-50 mm, preferably 5-20 mm.

7. The method for preparing a sintered foil for positive electrode material of an aluminum electrolytic capacitor according to claim 1, characterized in that: The chemical formation treatment includes low-pressure chemical formation, medium-pressure chemical formation and high-pressure chemical formation; Low-pressure chemical formation: immerse the sintered coiled foil in an aqueous solution containing 1.2-1.8 mol / L phosphoric acid, 0.5-1 mol / L ammonium adipate, and 0.1-0.3 mol / L boric acid. Pass a voltage of 100-200 V into the chemical formation solution and control the current density to 1-5 A / dm 2 , control the forming temperature to 50℃-70℃, and the forming time to 0.5-1h; medium pressure forming, immerse the coiled foil after low pressure forming in an aqueous solution containing 1-2mol / L sulfuric acid, 0.6-1.2mol / L sebacic acid, and 0.1-0.5mol / L citric acid, pass a voltage of 200-400V in the forming solution, and control the current density to 3-6A / dm 2 , control the forming temperature to 60-80℃, the forming time to 0.5-1h; high pressure forming, immerse the coiled foil after medium pressure forming in an aqueous solution containing 1-2mol / L sulfuric acid, 0.5-1.5mol / L citric acid, and 0.3-0.8mol / L boric acid, pass a voltage of 400-600V in the forming solution, and control the current density to 5-10A / dm 2 , control the formation temperature to 70-90℃, and the formation time to 1-2h.

8. The method for preparing a sintered foil for positive electrode material of an aluminum electrolytic capacitor according to claim 1, characterized in that: The sintering process is carried out under nitrogen or inert atmosphere, and the pressure is controlled to be 0.1-1 atmosphere; During sintering, first raise the temperature in the sintering furnace to 300-400°C for 1-2 hours, then gradually raise the temperature to 500-600°C and control the sintering time to 9-11 hours; After sintering, the cooling rate is controlled not to exceed 10°C / min until the temperature drops below 200°C, and then the sintered coil foil is taken out and cooled to room temperature.

9. The method for preparing a sintered foil for positive electrode material of an aluminum electrolytic capacitor according to claim 1, characterized in that: The temperature of the drying treatment in S4 is 80-120° C., the drying time is 15-45 min, and the protective atmosphere is nitrogen or inert gas.

10. A sintered foil for positive electrode material of aluminum electrolytic capacitor, characterized in that: The sintered foil is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Slurry for sintered foil and preparation method thereof

    CN119361325A

  • Composite three-dimensional foil electrode material for aluminum electrolytic capacitor and preparation method of composite three-dimensional foil electrode material

    CN122177665A